2001
DOI: 10.1097/00006534-200106000-00019
|View full text |Cite
|
Sign up to set email alerts
|

Free Anterolateral Thigh Flap for Extremity Reconstruction: Clinical Experience and Functional Assessment of Donor Site

Abstract: From August of 1995 through July of 1998, 38 free anterolateral thigh flaps were transferred to reconstruct soft-tissue defects. The overall success rate was 97 percent. Among 38 anterolateral thigh flaps, four were elevated as cutaneous flaps based on the septocutaneous perforators. The other 34 were harvested as myocutaneous flaps including a cuff of vastus lateralis muscle (15 to 40 cm3), either because of bulk requirements (33 cases) or because of the absence of a septocutaneous perforator (one case). Howe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
159
1
4

Year Published

2004
2004
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 233 publications
(176 citation statements)
references
References 29 publications
9
159
1
4
Order By: Relevance
“…Donor site complications are rare after harvesting the anterolateral thigh flap. 17,18,20,26,27 Although the radial forearm flap donor site morbidities are generally minor, tendon exposure and adhesions, sensory nerve damage, minor functional deficits, and a highly visible scar on the forearm [28][29][30][31] are frequent complaints. The radial forearm flap also has a reputation of having a high fistula rate, ranging from 17% to 50%.…”
Section: Discussionmentioning
confidence: 99%
“…Donor site complications are rare after harvesting the anterolateral thigh flap. 17,18,20,26,27 Although the radial forearm flap donor site morbidities are generally minor, tendon exposure and adhesions, sensory nerve damage, minor functional deficits, and a highly visible scar on the forearm [28][29][30][31] are frequent complaints. The radial forearm flap also has a reputation of having a high fistula rate, ranging from 17% to 50%.…”
Section: Discussionmentioning
confidence: 99%
“…The vastus lateralis is the biggest of these muscles and, if damaged, could result in patella and knee instability, as well as decreased knee extension (17,49). Perforator vessels to the ALT flap are septocutaneous (between rectus femoris and vastus lateralis) or musculocutaneous, the latter running through the vastus lateralis, and require intramuscular dissection with potential damage to the muscle (19,26,34).…”
Section: Vastus Lateralis Musclementioning
confidence: 99%
“…Some authors have subjectively concluded that the degree of donor site dysfunction was related to the degree of vastus lateralis damage (14,19); however, others found no such differences (30). Two studies carried out quantitative functional assessments comparing thighs from which an ALT flap was harvested with normal thighs, and found no statistically significant differences in function (17,34).…”
Section: Vastus Lateralis Musclementioning
confidence: 99%
See 1 more Smart Citation
“…Subsequently, after being able to reattach amputated parts, surgeons learned to transfer tissue from one part of the body to another, so called autologous tissue transplantation. Coincidentally, the anterior lateral thigh flap was described by the Chinese, and has become the ''work horse'' soft tissue flap, particularly as it relates to vascularized skin transfer in the modern microsurgical world [6,7]. Previous skin flaps such as the radial forearm flap, the scapular flap, and the groin flap are all microvascular tissue transfers that can be performed, but do not provide the surface area that the anterior lateral thigh flap supplies.…”
Section: Plastic Surgery Commentarymentioning
confidence: 99%